Notes on colombia’s dwelling problem (2004)
The dwelling problem in Colombia involves state policies, financial issues, internal economy, cultural aspects, displacement problem that causes violence and poverty, society values, among others. The State attitude towards dwelling deficit, the banks participation, private builders and politicians intervention through history, are some of the arguments considered in a problem that affects more than 10% of the nation inhabitants.